2021
DOI: 10.3390/agriculture11040372
|View full text |Cite
|
Sign up to set email alerts
|

Connecting Bio-Priming Approach with Integrated Nutrient Management for Improved Nutrient Use Efficiency in Crop Species

Abstract: The increasing demand for qualitative and varietal foods by the consumer society is a big concern for energy production, and utilization of that energy in a judicious manner for sustainable management of resources is a big challenge in the eminent future. Existing resources (land, water, fertilizer, etc.) and their socioeconomic aspects warrant the farming community to adopt alternative strategies aimed at enhancing the use efficiency of inputs and improve the environmental quality. The adaptability of microbe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
18
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
4

Relationship

2
7

Authors

Journals

citations
Cited by 45 publications
(20 citation statements)
references
References 86 publications
0
18
0
2
Order By: Relevance
“…The amount of mineral fertilizer for crop production has increased annually. However, the average recovery efficiencies range from 20% to 50%, depending on the nutrient ( Sarkar et al, 2021 ). Some recent studies have shown improved nutrient use efficiency due to microbial inoculation of plants ( Adesemoye and Kloepper, 2009 ; Abo-Kora, 2016 ; Paungfoo-Lonhienne et al, 2019 ; Pereira et al, 2020 ; Sarkar et al, 2021 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The amount of mineral fertilizer for crop production has increased annually. However, the average recovery efficiencies range from 20% to 50%, depending on the nutrient ( Sarkar et al, 2021 ). Some recent studies have shown improved nutrient use efficiency due to microbial inoculation of plants ( Adesemoye and Kloepper, 2009 ; Abo-Kora, 2016 ; Paungfoo-Lonhienne et al, 2019 ; Pereira et al, 2020 ; Sarkar et al, 2021 ).…”
Section: Discussionmentioning
confidence: 99%
“…However, the average recovery efficiencies range from 20% to 50%, depending on the nutrient ( Sarkar et al, 2021 ). Some recent studies have shown improved nutrient use efficiency due to microbial inoculation of plants ( Adesemoye and Kloepper, 2009 ; Abo-Kora, 2016 ; Paungfoo-Lonhienne et al, 2019 ; Pereira et al, 2020 ; Sarkar et al, 2021 ). However, these studies did not evaluate the effect of high inoculum concentrations on plant growth.…”
Section: Discussionmentioning
confidence: 99%
“…nutrient supply, atmospheric conditions, and competitiveness with other components of these communities [50]. In roots, carbon exudates are released which act as a nutrient source, as well as chemo-attractant, for bacteria, and are responsible for the colonization of endophytes inside the plant [46,[51][52][53]. Moreover, higher bacterial diversity in the upper part as compared to the middle part of the shoot might have originated from aerial colonization in the plants [54].…”
Section: Discussionmentioning
confidence: 99%
“…Among agricultural crops, nutrient efficiency use is less than 50% in most agricultural regions (Baligar et al, 2001). Factors such as energy crises and reduction of nutrient efficiency form a great challenge for modern agriculture (Sarkar et al, 2021b). Some studies have demonstrated that the consumption of fossil fuels, changes in the climate scenario, soil degradation, and food security have resulted in a cyclical degradation process of natural resources, low productivity, and low nutrient efficiency use (Rakshit, 2019).…”
Section: Nutrient Use E Ciencymentioning
confidence: 99%